CROTON TIGLIUM (LINN) SEED AS AN IDEAL ERADICANT OF PESTS AND PREDATORS IN FISH FARM - DIVAKARAN, O; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
The toxicity of Croton tiglium seed is very effective in the eradication of most of the aquatic fauna except a few species of hard shelled crustaceans such as crabs and prawns which are resistant to even very high concentrations of it. Its toxicity ranged between 0.4 and 2.2 p.p.m. for different species of fishes. Application of homogenised C. tiglium seed at the rate of 10 kg/ha (0.5 m depth) is found effective for the eradication of aquatic pests and predators of fish farms. While its toxicity lasts for 5-8 days in still water ponds, it is only for 1-3 days in tidal ponds with frequent replenishment of water. This method is thus most useful for the initial preparation of the ponds for pisciculture.